Sterile protection and transmission blockade by a multistage anti-malarial vaccine in the pre-clinical study - Iyori, Mitsuhiro; Blagborough, Andrew M.; Mizuno, Tetsushi; Abe, Yu-ichi; Nagaoka, Mio; Hori, Naoto; Yamagoshi, Iroha; Da, Dari F.; Gregory, William F.; Hasyim, Ammar A.; Yamamoto, Yutaro; Sakamoto, Akihiko; et al. (Frontiers in Immunology, 2022)
The Malaria Vaccine Technology Roadmap 2013 (World Health Organization) aims to develop safe and effective vaccines by 2030 that will offer at least 75% protective efficacy against clinical malaria and reduce parasite transmission. Here, we demonstrate a highly effective multistage vaccine against both the pre-erythrocytic and sexual stages of Plasmodium falciparum that protects and reduces transmission in a murine model. The vaccine is based on a viral-vectored vaccine platform, comprising a highly-attenuated vaccinia virus strain, LC16m8∆ (m8∆), a genetically stable variant of a licensed and highly effective Japanese smallpox vaccine LC16m8, and an adeno-associated virus (AAV), a viral vector for human gene therapy. The genes encoding P. falciparum circumsporozoite protein (PfCSP) and the ookinete protein P25 (Pfs25) are expressed as a Pfs25–PfCSP fusion protein, and the heterologous m8∆-prime/AAV-boost immunization regimen in mice provided both 100% protection against PfCSP-transgenic P. berghei sporozoites and up to 100% transmission blocking efficacy, as determined by a direct membrane feeding assay using parasites from P. falciparum-positive, naturally-infected donors from endemic settings. Remarkably, the persistence of vaccine-induced immune responses were over 7 months and additionally provided complete protection against repeated parasite challenge in a murine model. We propose that application of the m8∆/AAV malaria multistage vaccine platform has the potential to contribute to the landmark goals of the malaria vaccine technology roadmap, to achieve life-long sterile protection and high-level transmission blocking efficacy.